Life-sized Neolithic camel sculptures in Arabia: A scientific assessment of the craftsmanship and age of the Camel Site reliefs. (April 2022) - Guagnin, Maria; Charloux, Guillaume; AlSharekh, Abdullah M.; Crassard, Rémy; Hilbert, Yamandú H.; Andreae, Meinrat O.; AlAmri, Abdullah; Preusser, Frank; Dubois, Fulbert; Burgos, Franck; Flohr, Pascal; Mora, Pascal; et al.
Highlights: Chronological assessment and pXRF analysis suggest reliefs date to the Neolithic. Neolithic arrowheads and radiocarbon dates attest occupation 5200–5600 BCE. Reliefs were carved with stone tools and re-shaped over a longer period of time. Luminescence dating suggests erosion caused reliefs to fall around 1000 BCE. Camel Site likely has the oldest known surviving large-scale animal reliefs in the world. Abstract: The life-sized, naturalistic reliefs at the Camel Site in northern Arabia have been severely damaged by erosion. This, coupled with substantial destruction of the surrounding archaeological landscape, has made a chronological assessment of the site difficult. To overcome these problems, we combined results from a wide range of methods, including analysis of surviving tool marks, assessment of weathering and erosion patterns, portable X-ray fluorescence spectrometry, and luminescence dating of fallen fragments. In addition, test excavations identified a homogenous lithic assemblage and faunal remains that were sampled for radiocarbon dating. Our results show that the reliefs were carved with stone tools and that the creation of the reliefs, as well as the main period of activity at the site, date to the Neolithic. Neolithic arrowheads and radiocarbon dates attest occupation between 5200 and 5600 BCE. This is consistent with measurements of the areal density of manganese and iron in the rock varnish. The site was likely in use over a longer period and reliefs were re-worked when erosion began to obscure detailed features. By 1000 BCE, erosion was advanced enough to cause first panels to fall, in a process that continues until today. The Camel Site is likely home to the oldest surviving large-scale (naturalistic) animal reliefs in the world.